PENGARUH LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Naufal Abdillah (2020)
This research was conducted aiming to prove the effect of leverage, profitability and company size on financial distress. The population in this study is all companies included in the service sector which are listed on the Indonesia Stock Exchange in 2016 to 2018. Purposive sampling technique is a sampling technique in the study so that there are 220 companies with 3 years of observation. The independent variable influencing the dependent variable in this study is shown at 51.7% and the remaining 48.3% is influenced by other variables outside this study. The results of this study explain that the leverage and profitability ratios have a significant effect on financial distress. While the size of the company has no effect on financial distress.